Gallium-67 myocardial imaging for the detection of myocarditis in the acute phase of Kawasaki disease (mucocutaneous lymph node syndrome): the usefulness of single photon emission computed tomography. Issue 4 (October 1987) - Matsuura, H; Ishikita, T; Yamamoto, S; Umezawa, T; Ito, R; Hashiguchi, R; Saji, T; Matsuo, N; Takano, M
Abstract : Myocardial imaging with gallium-67 citrate was used to detect myocarditis in 46 consecutive infants and children (31 boys and 15 girls, mean age 21 months) with Kawasaki disease. In all of them planar imaging (group A) was performed at 6 hours and at 48 or 72 hours after the intravenous administration of a mean (SD) dose of gallium-67 citrate (0.07 (0.02) mCi/kg). Thirty four patients (24 boys and 10 girls, mean age 21 months) also had single photon emission computed tomography imaging (group B) soon after planar imaging. The patients had been ill for from 5 days to 16 days (mean (SD) 10.5 (2.4) days in group A and 10.6 (3.0) days in group B). The colour images obtained at 48 or 72 hours were positive in 41% of group A and in 64% of group B. Among the patients with clinically suspected myocarditis, 63% in group A and 80% in group B had positive myocardial images. Single photon emission computed tomography imaging permitted the identification of tracer in the myocardium, the pericardium only, or in the heart chambers. Myocardial imaging with gallium-67 citrate, especially when used with single photon emission computed tomography imaging, is useful for the detection of myocarditis in the acute phase of Kawasaki disease.